2023
DOI: 10.3390/cells12101365
|View full text |Cite
|
Sign up to set email alerts
|

Organ Abnormalities Caused by Turner Syndrome

Abstract: Turner syndrome (TS), a genetic disorder due to incomplete dosage compensation of X-linked genes, affects multiple organ systems, leading to hypogonadotropic hypogonadism, short stature, cardiovascular and vascular abnormalities, liver disease, renal abnormalities, brain abnormalities, and skeletal problems. Patients with TS experience premature ovarian failure with a rapid decline in ovarian function caused by germ cell depletion, and pregnancies carry a high risk of adverse maternal and fetal outcomes. Aorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 194 publications
0
0
0
Order By: Relevance
“…[ 10 ] Following renal denervation in a 6-year-old girl with Turner syndrome, her BP returned to normal 12 months after the operation. [ 11 ] Therefore, reducing the excitability of the sympathetic nervous system in patients with Turner syndrome and inhibiting the activation of the RAAS may be potential targets for treating hypertension in patients with Turner syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Following renal denervation in a 6-year-old girl with Turner syndrome, her BP returned to normal 12 months after the operation. [ 11 ] Therefore, reducing the excitability of the sympathetic nervous system in patients with Turner syndrome and inhibiting the activation of the RAAS may be potential targets for treating hypertension in patients with Turner syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dimorphism and gender-dependent variations associated with responses to different stressors are aspects involved in the pathophysiological gender differences found in PAD. Sex chromosomes play an important role in vascular structural and functional damage that is predisposed to atherosclerosis [28][29][30]. Based on the concept that the onset of menopause and reduced estrogen production increases cardiovascular risk in women [31], Taddei et al [32] demonstrated that age-associated endothelial dysfunction is attenuated before menopause in normotensive or hypertensive patients compared to men.…”
Section: Discussionmentioning
confidence: 99%